INFLUENCE OF FINISHING TECHNIQUES OF TI-BASED ALLOYS USED IN PROSTHETIC RESTORATIONS ON THE FORMATION OF CANDIDA ALBICANS BIOFILM - Elena-Raluca Baciu; Maria Baciu; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2011)
Surface roughness plays an important role in the formation of specific oral cavity biofilm. The paper aims at analyzing the influence of mechanical finishing techniques on the formation of Candida albicans biofilms. We studied two different Ti-based alloys used in prosthetic restorations and two finishing techniques: mechanical polishing with rubber polisher and mechanical polishing with cotton polisher and polishing paste. Examinations on roughness have made reference to Rz. The ability to adhere and to form the Candida albicans biofilms onto the rough surfaces of the studied samples was highlighted by scanning electron microscopy (SEM). Microbiological analysis indicates the strong relationship between the surface quality of dental alloys used in prosthetic restorations and the ability of the fungal pathogen of Candida albicans type to adhere to these metal surfaces.